Hospital Adaptation Strategies in the Face of Changes in Health Policies - Victoria Cyntia Yogya Astuti; Yunita Indah Dewi; Purwadhi Purwadhi; Yani Restiani Widjaja (Journal of Economics and Social Sciences (JESS), 2026)
This study aims to analyze hospital adaptation strategies in facing changes in health policies, identify obstacles encountered during these processes, and formulate efforts to improve organizational readiness and resilience. A qualitative approach is utilized to explore the phenomena of adaptation, involving data collection through literature reviews of relevant books and scientific journals analyzed descriptively. Results indicate that managerial agility, digital transformation, and the strengthening of human resource capacity are the primary pillars for hospitals to maintain operational stability amidst frequently shifting regulations. Challenges frequently encountered include internal staff resistance to change, limitations in information technology infrastructure, financial pressure due to uncertain claim schemes, and overlapping bureaucracy between central and regional governments. Strategic efforts that can be pursued include establishing a regulation adaptation task force, investing in integrated information systems, and building a communicative and adaptive work culture. Collaboration through strategic partnerships between health facilities and periodic data-based performance evaluations are proven to strengthen the bargaining position and service effectiveness even when institutions are under pressure from dynamic policies.